Application of iteration method for solving the problem of deformation of unidirectional composites with nonlinear viscoelastic matrix - Kulikov, Roman Georgievich; Trufanov, Nikolay Alexandrovich (Computational Continuum Mechanics, 2011)
Some numerical aspects of an iteration method that is based on the idea of physical immersion method and applied to nonlinear viscoelastic problems are examined by solving the problem of deformation of the periodic unit cell of a fiber composite with a nonlinear viscoelastic matrix. A numerical solution procedure, suggesting that the initial nonlinear non-homogeneous viscoelastic problem is reduced to an iterative sequence of linear elastic problems for homogeneous isotropic materials, is realized. Relaxation processes, taking place in the elementary cell of a fiber composite at various deformation levels, are examined.